Adult males with haemophilia have a different macrovascular and microvascular endothelial function profile compared with healthy controls. Issue 5 (16th June 2017) - Sun, H.; Yang, M.; Fung, M.; Chan, S.; Jawi, M.; Anderson, T.; Poon, M.‐C.; Jackson, S.
Abstract : Introduction: Endothelial function has been identified as an independent predictor of cardiovascular risk in the general population. It is unclear if the haemophilia population has a different endothelial function profile compared to the healthy population. Aim: This prospective study aims to assess if there is a difference in endothelial function between haemophilia patients and healthy controls, and the impact of endothelial function on vascular outcomes in the haemophilia population. Baseline cardiovascular risk factors and endothelial function were presented. Methods: Adult males with haemophilia A or B recruited from the British Columbia and Southern Alberta haemophilia treatment centres were matched to healthy male controls by age and cardiovascular risk factors. Macrovascular endothelial function was assessed by brachial artery flow‐mediated dilation (FMD) and nitroglycerin‐mediated dilation (NMD), and microvascular endothelial function was assessed by hyperaemic velocity time integral (VTI). Multivariable linear regression was used to assess the association between haemophilia and endothelial function. Results: A total of 81 patients with haemophilia and 243 controls were included. Patients with haemophilia had a similar FMD and NMD compared to controls, although haemophilia was associated with higher FMD on multivariable analysis. Haemophilia was associated with significantly lower VTI on univariate and multivariable analyses, regardless of haemophilia type and severity. Conclusions: Adult males with haemophilia appear to have lower microvascular endothelial function compared to healthy controls. Future studies to assess the impact of endothelial dysfunction on cardiovascular events in the haemophilia population are needed.